Countries’ strategies in facing crisis and disasters during the Corona Virus pandemic - The case of the Kingdom of Bahrain - - Beshr, Baligh Ali Hasan (Journal of Risk and Crisis Management, 2020)
The aim of this research us to identify the most important mechanisms and tools used by countries in facing the crisis of Corona Virus Pandemic (case study of the Kingdom of Bahrain) to review the most important aspects of the crisis and the mechanisms to overcome it while this crisis transformed to be economical, social, and environmental crisis impacting the sociality. The research problem summarized in what are the strategies taken by the Kingdom of Bahrain in containing and facing the crisis which it gives back the international organizations praise. The methodology used in this research is the descriptive analytical approach to describe the phenomena, the reasons behind it and the mechanism used to face it. The most important results of this research are, the international economy has suffered huge losses reached 50 billion dollars. Western governments have been unable to manage the crisis and have turned basic rights to health and life into a selective process. The unemployment rate rose to 1.2 points. The number of infected cases in the world has increased to 6, 925, 880 cases to date. As well as Bahrain has a strong infrastructure to cope with crises at all levels. Finally, kingdom of Bahrain has taken careful procedures and measures steps to manage the crisis. The research has given recommendations to increase the attention to scientific research in the field of crisis management and to rely on other sources of income instead of oil so as not to be affected by economic fluctuations and crises, and to conduct more research in the mechanisms of facing the emergencies and crisis and the readiness of after COVID- 19 Corona Virus.